Current Views of Scapular Dyskinesis and its Possible Clinical Relevance - Aaron Sciascia; W. Ben Kibler (International Journal of Sports Physical Therapy)
Scapular dyskinesis is a condition that is frequently observed clinically but not often understood. Too often it is viewed as a diagnosis which is not accurate because it is a physical impairment. This misclassification of dyskinesis has resulted in literature that simultaneously supports and refutes scapular dyskinesis as a relevant clinical entity as it relates to arm function. These conflicting views have not provided clear recommendations for optimal evaluation and treatment methods. The authors’ experience and scholarship related to scapular function and dysfunction support that scapular dyskinesis is an impairment that has causative factors, that a pathoanatomical approach should not be the primary focus but should be considered as part of a comprehensive examination, that a qualitative examination for determining the presence or absence of a scapular contribution to shoulder dysfunction is currently the best option widely available to clinicians, and that rehabilitation approaches should be reconsidered where enhancing motor control becomes the primary focus rather than increasing strength.